Synthesis and Physicochemical Behaviour of Polyurethane-Multiwalled Carbon Nanotubes Nanocomposites Based on Renewable Castor Oil Polyols - Alaa, Ali; Kamal, Yusoh; S. F., Hasany (Hindawi Publishing Corporation, 2014)
Polyurethanes (PUs) are high performance materials, with vast industrial and engineering applications. In this research, effects of Multiwalled Carbon Nanotubes (MWCNTs) on physicochemical properties of Castor Oil based Polyurethanes (COPUs) were studied. MWCNTs were added in different weight percentages (0% to 1% wt) in a castor oil based polyurethane (COPUs-MWCNTs) nanocomposites. The composition, structure, and morphology of polyurethanes were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM), and element detection by energy dispersive spectroscopy (EDX) analysis, respectively. Thermal stability was studied by thermogravimetric analysis (TGA). Barrier properties and surface area studies were investigated by nitrogen permeability machine and BET technique. Mechanical properties were calculated by tensile universal testing machine. Results showed well dispersed MWCNTs in polyurethane matrix at different weight percentages. The best results were obtained with 0.3 wt% of MWCNTs in the composite. Surface area studies revealed presence of very few pores which is in a good agreement with barrier permeability, reduced up to ~68% in 1 wt% and ~70% in 0.5 wt% of MWCNTs in polymer matrix, with respect to pure COPUs samples.